Transitioning from Italy to the United States: Intercultural learning and living experience of two doctoral students - Qiu, Ruoyi; SCHIAVO, MARTINA; Coryell, Joellen (Journal of International Students, 2024)
This reflection analyzes the perspectives of two doctoral students, Chinese and Italian, who are international students and conduct research in the United States. Moreover, this reflection conducts Kolb’s (1984) model of experiential learning, aims to draw comparisons to our respective intercultural learning and living experiences, and highlights how intertwined we are despite different cultural backgrounds. Moreover, the reflection helps to explain better and understand our variable intercultural experiences and comes out with a conclusion that understanding ourselves as the first step to improve intercultural competence.